Primary mixed-type autoimmune hemolytic anemia concomitant with acute splanchnic veins thrombosis of idiopathic origin in a young woman: an unexplained association.. - Pasquale Niscola (Mediterranean Journal of Hematology and Infectious Diseases)
An unexplained association of primary mixed-type autoimmune hemolytic anemia with acute splanchnic veins thrombosis of idiopathic origin in a young woman is described.